2002
DOI: 10.1111/j.1749-6632.2002.tb04741.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Sodium‐Calcium Exchanger Associates with Caveolin‐3

Abstract: The cardiac Na/Ca exchanger's (NCX1) role in calcium homeostasis during myocardial contractility makes it a possible target of signaling factors regulating inotropy. Caveolae, structured invaginations of the plasmalemma, are known to concentrate a wide variety of signaling factors. The predominant coat proteins of caveolae, caveolins, dock to and regulate the activity of these signaling factors and other proteins through interaction with their scaffolding domain. In this study we investigated the interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…Additionally, calcineurin, 14-3-3⑀ and F-actin have been shown to associate with the Na/Ca exchanger and modulate its activity (56 -58). Finally, both caveolin 3 and annexin A5 may also associate with Na/Ca exchanger in vivo (59,60). Although it is likely that one or more of these proteins may influence the cellular pathways responsible for the localization and stability of Na/Ca exchanger in cardiomyocytes, in vivo data to support the physiological relevance of these interactions is not yet available.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, calcineurin, 14-3-3⑀ and F-actin have been shown to associate with the Na/Ca exchanger and modulate its activity (56 -58). Finally, both caveolin 3 and annexin A5 may also associate with Na/Ca exchanger in vivo (59,60). Although it is likely that one or more of these proteins may influence the cellular pathways responsible for the localization and stability of Na/Ca exchanger in cardiomyocytes, in vivo data to support the physiological relevance of these interactions is not yet available.…”
Section: Discussionmentioning
confidence: 93%
“…[14][15][16][17] In cardiomyocites, the ion channels HCN4, Ca v 1.2, K v 1.5, kir6.2/Sur2a, Na v 1.5, and NCX are targeted to caveolae, and Cav-3 directly interacts with b 2 -adrenoreceptors with whom it regulates the sarcolemmal targeting of cyclic AMP signal. [18][19][20][21][22] Notably, chemical disruption of caveolae affects the excitation-contraction coupling and b-adrenergic responsiveness of adult cardiac myocites. 21,22 Likewise, Cav-3 has a role in the regulation of energy metabolism of muscle cells.…”
Section: Caveolin-3 In Muscle Development and Physiologymentioning
confidence: 99%
“…The cardiac NCX associates with caveolin-3, and caveolin-binding motifs are located in the endogenous XIP region (residues 223-231), but also within the herein identified XIP-regulatory domain (residues 620 -627). 31 It was suggested that by its association with the endogenous XIP region (or possibly also its regulatory domain), caveolin-3 may activate the NCX by inhibiting the interaction of the endogenous XIP region with its binding site. 31 If this holds true, then higher membrane content of caveolin-3 in cardiac myocytes may reduce the inhibitory efficacy of exogenous XIP compared with HEK cells, where caveolin-3 is virtually absent.…”
Section: Regulation Of Ncx By Xipmentioning
confidence: 99%
“…31 It was suggested that by its association with the endogenous XIP region (or possibly also its regulatory domain), caveolin-3 may activate the NCX by inhibiting the interaction of the endogenous XIP region with its binding site. 31 If this holds true, then higher membrane content of caveolin-3 in cardiac myocytes may reduce the inhibitory efficacy of exogenous XIP compared with HEK cells, where caveolin-3 is virtually absent. 32 In a similar way, ATP-and PIP 2 -induced activation of I NCX are supposedly attributable to interaction of PIP 2 with the endogenous XIP region, thus inhibiting its interaction with the XIP regulatory site.…”
Section: Regulation Of Ncx By Xipmentioning
confidence: 99%